Tumour cell invasion into blood vessels is significantly related to breast cancer subtypes and decreased survival. Issue 4 (9th September 2016) - Klingen, Tor A; Chen, Ying; Stefansson, Ingunn M; Knutsvik, Gøril; Collett, Karin; Abrahamsen, Anne L; Aase, Hildegunn; Aas, Hans; Aas, Turid; Wik, Elisabeth; Akslen, Lars A
Abstract : Aims: Vascular invasion in breast cancer is associated with increased risk of recurrence, metastases and death from disease. However, there are few studies discriminating between blood vessel invasion (BVI) and lymphatic vessel involvement (LVI). Methods: A population-based series of 282 breast cancers was examined (200 screen-detected and 82 interval patients) with respect to BVI and LVI in addition to basic features and molecular subtypes, using CD31 and D2-40 antibodies. This series is part of the prospective Norwegian Breast Cancer Screening Program. Results: The frequency of LVI and BVI was 25% and 15%, respectively. BVI was associated with HER2-positive and basal-like tumours, and several features of aggressive breast cancer, whereas LVI showed weaker associations. BVI was the strongest factor to predict interval cancer presentation. BVI showed significant associations with recurrence-free survival and disease-specific survival in univariate and multivariate analyses, whereas LVI was not significant. Conclusions: Our findings indicate that BVI by tumour cells is strongly associated with aggressive tumour features including a basal-like phenotype, and BVI was an independent prognostic factor in contrast to what was found for LVI.